Enhancing the mechanical properties of electrospun polyester mats by heat treatment - M. Kancheva; A. Toncheva; N. Manolova; I. Rashkov (eXPRESS Polymer Letters)
Microfibrous materials with a targeted design based on poly(L-lactic acid) (PLA) and poly(ε-caprolactone) (PCL) were prepared by electrospinning and by combining electrospinning and electrospraying. Several approaches were used: (i) electrospinning of a common solution of the two polymers, (ii) simultaneous electrospinning of two separate solutions of PLA and PCL, (iii) electrospinning of PLA solution in conjunction with electrospraying of PCL solution, and (iv) alternating layer-by-layer deposition by electrospinning of separate PLA and PCL solutions. The mats were heated at the melting temperature of PCL (60°"), thus achieving melting of PCL fibers/particles and thermal sealing of the fibers. The mats subjected to thermal treatment were characterized by greater mean fiber diameters and reduced values of the water contact angle compared to the pristine mats. Heat treatment of the mats affected their thermal stability and led to an increase in the crystallinity degree of PLA incorporated in the mats, whereas that of PCL was reduced. All mats were characterized by enhanced mechanical properties after thermal treatment as compared to the non-treated fibrous materials.